POLICY ON FOREIGN LANGUAGE EDUCATION IN INDONESIA - Alwasilah, Chaedar (International Journal of Education, 2013)
To understand the state of the art of TEFL at elementary and junior secondary schools, a surveywas administered to two groups of EFL teacher respondents, namely 88 elementary teachersin Jakarta and 200 junior secondary teachers who live in Jakarta and West Java, and Bantenprovinces. They teach at either private schools (50.8%) or public schools (49.2%), and 89.0 %of them have worked for more than fi ve years. They are either public (47.4%) or private teachers(52.6%), and most of them are female teachers (69.8%). The junior secondary teachers wereparticipants of the nine-day Teacher Certifi cation Program in September 2011, a mandatoryprofessional development scheme to qualify them as a professional teacher. The primary schoolteachers are graduates of or are attending PGSD, i.e., four year elementary school teachereducation. The survey fi ndings are not generalizable to the whole country, but they present arelatively comprehensive picture of EFL teaching in the basic education units, i.e., elementaryand secondary schools.Keywords: Teaching English as Foreign Language (TEFL), Teacher Certifi cation Program,professional development, teacher education